ROR1 as a novel therapeutic target for EGFR-mutant non-small-cell lung cancer patients with the EGFR T790M mutation - Karachaliou, Niki (Transl Lung Cancer Res, 2014)
BACKGROUND: Activation of bypass signaling pathways, impairment of apoptosis and mutation of epidermal growth factor receptor (EGFR) to a drug-resistant state are well known mechanisms of resistance to single-agent erlotinib therapy in non-small-cell lung cancer (NSCLC) driven by EGFR mutations. Orphan receptor 1 (ROR1) knockdown inhibited the growth of NCI-H1975 cells (harboring EGFR L858R and T790M mutations). A pro-survival function for ROR1/MEK/ERK signaling in cooperation with AKT has been demonstrated. METHODS: We have assessed ROR1 expression in 45 patients from the EURTAC trial (clinicaltrials.gov NCT00446225), 27 of whom harbored pretreatment concomitant EGFR T790M mutations, and correlated results with outcome. RESULTS: Progression-free survival (PFS) was 11.8 months for erlotinib-treated patients with low/intermediate and 5.8 months for those with high ROR1 levels. PFS for chemotherapy-treated patients was 5.6 and 9 months, respectively (P=0.0165). A total of 15 erlotinib-treated patients harbored concomitant T790M mutations; for these patients, PFS was 10.8 months for those with low/intermediate compared to 2.7 months for those with high ROR1 levels. In contrast, among 12 chemotherapy-treated patients with concomitant T790M mutations, PFS was 5.8 months for those with low/intermediate, compared to 14.2 months for those with high ROR1 levels (P=0.0138). CONCLUSIONS: ROR1 expression has a differential effect on outcome to erlotinib and chemotherapy in EGFR-mutant NSCLC patients. High ROR1 expression significantly limits PFS in erlotinib-treated patients with T790M mutations and ROR1-directed therapies can enhance the efficacy of treatment. In contrast, high ROR1 expression confers longer PFS to chemotherapy in the same group of patients. The role of chemotherapy and erlotinib in EGFR-mutant NSCLC patients with high ROR1 expression warrants further investigation.